Pengembangan Media Pembelajaran Berbasis Web Google Sites Pada Pembelajaran IPAS Di Kelas IV SD - Yulia Darniyanti; Antik Estika Hader; Diana Putri (Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by the difficulties of students understanding learning material, especially in learning IPAS. This is because in the learning process educators have not used creative and interesting media, educators only use sober media such as textbooks and media images. This study aims to develop google sites web-based learning media for IPAS learning in class IV SD. This type of research and development uses Research And Development (R&D) type of research. This google sites web-based media development model uses the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The type of data used is qualitative and quantitative data. The instruments used are validity, practicality and effectiveness sheets. Data collection techniques used are interviews, observation, questionnaires, documentation and tests. Analysis of the data used in the form of analysis of validity, practicality and effectiveness. As for the results of the development of google sites web-based media obtained from 3 validators, google sites web-based media obtained a percentage with an average of 87.85% with a very valid category. The practicality results assessed from the teacher response questionnaire obtained an average percentage of 93.33% in the very practical category and the student response questionnaire obtained a percentage of 93.72% in the very practical category. The effectiveness results were obtained from the completeness of the results of students with an average of 88.89% in the very effective category, so it can be concluded that google sites web-based media can be said to be valid, practical and effective.